CSC569: Principles of Compilers / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
The construction of a compiler involves three important phases. The lexical analysis phase deals with the identifying of lexeme items, the syntax analysis phase determines the underlying structure of the source program and the code generation phase produces the machine code. The syllabus covers from the evolution of program languages to the basics of a compiler: lexical analysis, syntax analysis, scanner and parser.